Determinants of corporate cash holdings: evidence from Vietnamese materials firms - Tran , Hue Chi; Phan , Tran Trung Dzung (Journal of International Economics and Management, 2021)
This paper investigates factors affecting cash holdings of materials firms listed on Vietnamese stock exchanges. The study shows that leverage, profitability, cash conversion cycle, cash flows, and growth opportunities significantly affect the level of cash holdings of Vietnamese materials companies by analyzing data collected from 51 companies over seven years (2013-2019) and using FGLS procedure on fixed effect estimation. This study adds more insights in the field of liquidity management in general and cash management in particular by determining factors influencing cash holdings. Outcomes from this research would help managers, investors, and consultants make corporate governance decisions.